PROJECT OF SCIENTIFIC AND EDUCATIONAL COURSE "ANALYTICAL HISTORY OF PHILOSOPHY" - Kononenko, T. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
The purpose of the article is to inform about the project of the scientific and educational course "Analytical history of philosophy".